#### Answer

(3, 1)

#### Work Step by Step

Rewrite x - y = 2 as x = 2 + y. Plug this into the second equation
2(2 + y) + 3y = 9
4 + 2y + 3y = 9
5y = 5
y = 1
Plug y = 1 back into x = 2 + y
x = 2 + 1 = 3
Solution is (3, 1)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(3, 1)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.